2012
DOI: 10.1007/s00299-012-1248-6
|View full text |Cite
|
Sign up to set email alerts
|

Direct and indirect organogenesis of Clivia miniata and assessment of DNA methylation changes in various regenerated plantlets

Abstract: Methylation variation in regenerated plantlets of C. miniata was found to be related to the types of explants, regeneration pathways and number of regeneration generations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 58 publications
0
13
0
Order By: Relevance
“…Rapid and reversible changes in DNA methylation were also shown in potato cell suspension (Law and Suttle 2005). Lowered genomic DNA methylation of regenerants derived from shoots compared to young leaves or petals was described in case of bush lily (Clivia miniata), suggesting that the variation in methylation of regenerated plantlets was related to the nature of the explants (Wang et al 2012).…”
Section: Dna Methylation Pattern Alterationsmentioning
confidence: 89%
“…Rapid and reversible changes in DNA methylation were also shown in potato cell suspension (Law and Suttle 2005). Lowered genomic DNA methylation of regenerants derived from shoots compared to young leaves or petals was described in case of bush lily (Clivia miniata), suggesting that the variation in methylation of regenerated plantlets was related to the nature of the explants (Wang et al 2012).…”
Section: Dna Methylation Pattern Alterationsmentioning
confidence: 89%
“…Culture-induced DNA methylation has been found in different species, including rice, maize, and barley [35][36][37]. Furthermore, many studies have shown that regeneration under various selection stresses or from various donor tissues induced changes in methylation patterns [38][39][40]. When uniform callus donor tissue was used in an Agrobacterium-mediated transformation procedure in rice [41,42], there was no difference in methylation among donor tissues between experiments.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro plant organogenesis corresponds to the formation of organs (buds, roots or shoots) from explants under controlled conditions (Sugiyama ). DNA methylation leading to changes in the chromatin state occurs in plant cells undergoing callus formation and organogenesis in vitro (Xu et al , Pischke et al , Maury et al , Wang et al ). In addition, DNA methylation in promoters participates in the establishment and/or maintenance of the undifferentiated state in plant cells (Berdasco et al ).…”
Section: Discussionmentioning
confidence: 99%